2015
DOI: 10.2340/00015555-2029
|View full text |Cite
|
Sign up to set email alerts
|

Swedish Experiences From Patch Testing Methylisothiazolinone Separately

Abstract: The preservative methylchloroisothiazolinone/methylisothiazolinone (MCI/MI) is a well-known sensitiser and present in the Swedish baseline series since the 1980s. The proportions of MCI/MI are 3:1. MI alone has been used as a preservative since less than 10 years. This study was conducted on behalf of the Swedish Contact Dermatitis Research Group to evaluate inclusion of MI in the Swedish baseline series since the preparation of MCI/MI might fail to detect contact-allergic reactions to MI alone. Patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Moreover, we started prospective MI patch testing separately as a routine examination and followed the test results for one year. The 4.8% prevalence of MI hypersensitivity is, though high, may be considered as rather moderate compared to other European data [ 11 , 16 22 ]. Among the MI sensitized patients the mean age was 39 years.…”
Section: Discussionmentioning
confidence: 57%
“…Moreover, we started prospective MI patch testing separately as a routine examination and followed the test results for one year. The 4.8% prevalence of MI hypersensitivity is, though high, may be considered as rather moderate compared to other European data [ 11 , 16 22 ]. Among the MI sensitized patients the mean age was 39 years.…”
Section: Discussionmentioning
confidence: 57%
“…was tested in parallel with MCI/MI 0.02% aq. 8 It showed that by only testing with MCI/MI at 0.02% there is a risk that those with a weak MI sensitization are missed because the concentration of MI is too low in the test preparation (50 ppm). The SCDRG concluded that because several repeated open application studies had shown that also patients with weak allergies risk developing dermatitis if exposed under prolonged conditions, [9][10][11] it is necessary to test with MI separately, and thus SCDRG recommended that MI 0.2% aq.…”
Section: Introductionmentioning
confidence: 99%
“…(60 μg/cm 2 ) should be included in the Swedish baseline series from January 2014. 8 This is the same concentration/dose as the one recommended in the European baseline series. 12 Thereby, at present there are two patch-test preparations containing MI in the Swedish and European baseline series.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another patch test for CMIT/MIT was performed on 1,498 Swedish patients with suspected allergic contact dermatitis. It was found that 7.1% of these patients responded to CMIT/MIT ( 23 ).…”
Section: Discussionmentioning
confidence: 99%